TOPOGRAPHIC MAPPING OF SLOPES IN LANDSLIDE PRONE AREAS USING THE SCHLUMBERGER CONFIGURATION GEOELECTRICS TECHNIQUE - Situmorang, Howard; Nasution, Habibi Azka; Nasution, Budiman; Aningsih, Sri; Ummi, Shofia (EINSTEIN (e-Journal), 2025)
Landslides in Lembang in 2020-2021 were influenced by intense heavy rainfall. The surface contours in the village are generally in steep surface conditions with varying slope angles. The purpose of this study was to determine the surface contour in two dimensions by using the geoelectric method with Schlumberger configuration. The first stage was carried out by recording data on 5 tracks with 3 parallel tracks up to 75 , one track intersecting the other track area up to 60 and one track next to the landslide at 52.5 . The results showed that the resistivity of the rocks varied between 0.465-1952 . Interpretation of rock 0.465-21.5 as clay and sand, 22-146 as sandstone, dry gravel, 156-380 as andesite, basalt and 389-1952 as granite, diorite, limestone. The contrasting differences in the variation of the values on each track are known as slip planes. Slip planes have been found on 5 tracks with depths ranging from 6 to 12 m. The results of the 2-dimensional surface modelling that has been carried out show that the research area has the potential for landslides